THE EFFECT OF THE PROJECT BASED LEARNING (PjBL) LEARNING MODEL ASSISTED BY PERFORMANCE ASSESSMENT ON THE LEARNING OUTCOMES OF GRADE VIII JUNIOR HIGH SCHOOL STUDENTS CONSTRUCTION OF UNP LABORATORIES ON ORGAN SYSTEM MATERIAL - Gita Widya Sari; Azza Nuzullah Putri; Yurnetti Yurnetti; Arief Muttaqiin; Rani Oktavia (SEMESTA: Journal of Science Education and Teaching, 2023)
Kurikulum merdeka was implemented in 2022. The characteristics of the kurikulum merdeka were the development of soft skills and character, focus on essential materials, and flexible learning. The low learning outcomes of students were still a problem. One of the efforts that can be done was to apply the Project Based Learning (PjBL) model assisted by performance assessment. This study aimed to determine the effect of the Project Based Learning (PjBL) model assisted by performance assessment on the learning outcomes of grade VIII students on organ system material. This type of research was Quasi Experiment, with a Non Equivalent Control Group Design research design. The sampling technique used was total sampling. The experimental class used the Project Based Learning (PjBL) model assisted by performance assessment while the control class used conventional methods. Based on the hypothesis test with the t test, the calculated value = 2.654 and ttable = 2.006. From the data shows that if tcalculate > ttable, h1 was accepted, it was concluded that there was an influence of the Project Based Learning (PjBL) model assisted by performance assessment on the cognitive learning outcomes of grade VIII students on organ system material.